(Meth)acrylate resin and dry film solder resist containing same

By adjusting the chemical structure and repeating units of the acrylate resin, the insulation and reliability problems caused by chloride ion formation in the prior art are solved, and higher insulation and adhesion are achieved, and the process flow is simplified.

JP2025503747APending Publication Date: 2025-02-04LG CHEM LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024542385
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-04-19
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

The existing acid-based acrylate resins produce a large amount of chloride ions during the manufacturing process, resulting in copper migration and poor insulation and reliability problems in the circuit, and serious problems in development and filler residues.

Method used

Using acrylate resins and repeat units with specific chemical structures, the base resin and reaction type can be adjusted to reduce chloride ion generation during the manufacturing process, and the active ester structure can improve adhesion with epoxy molding compounds to avoid plasma treatment.

Benefits of technology

Effectively reduce chloride ion generation, improve insulation and reliability, reduce filler residue, enhance adhesion with epoxy molding compounds, and simplify process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503747000001_ABST
    Figure 2025503747000001_ABST
Patent Text Reader

Abstract

The present invention relates to a (meth)acrylate-based resin and a dry film solder resist containing the same, and more particularly to a (meth)acrylate-based resin and a dry film solder resist containing the same in which generation of chloride ions is reduced by adjusting the types of base resin and reactants used in the manufacturing process.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This specification claims the benefit of the filing date of Korean Patent Application No. 10-2022-0083755, filed with the Korean Intellectual Property Office on July 7, 2022, the entire contents of which are incorporated herein by reference. The present invention relates to a (meth)acrylate-based resin and a dry film solder resist containing the same, and more particularly to a (meth)acrylate-based resin and a dry film solder resist containing the same in which generation of chloride ions is reduced by adjusting the types of base resin and reactants used in the manufacturing process. [Background technology]

[0002] 2. Description of the Related Art As various electronic devices become smaller and lighter, solder resists capable of forming fine opening patterns are being used on printed circuit boards, semiconductor package boards, flexible circuit boards, and the like. Solder resists are generally required to have properties such as developability, high resolution, insulating properties, adhesion, soldering heat resistance, and gold plating resistance.

[0003] The acid group-containing acrylate resin used in the existing solder resist has been prepared by acrylate of epoxy resin with acrylic acid, and then reacting with acid anhydride to prepare an acrylate containing an acid group. When prepared by this method, a large amount of chlorine ions are contained during the manufacturing process of the epoxy resin, which causes migration of copper contained in the circuit, resulting in a problem of reduced insulation and poor reliability. In addition, when the acid group-containing acrylate contains a large amount of acid groups, problems occur with filler residue, and when the acid group is contained in a small amount, problems occur with reduced developability.

[0004] Therefore, there is a need for an improved method for producing an acrylate resin in order to produce a solder resist having improved developability, residue reduction and insulating properties. Summary of the Invention [Problem to be solved by the invention]

[0005] The technical problem to be solved by the present invention is to provide a (meth)acrylate-based resin and a dry film solder resist containing the same, which can improve insulation reliability by controlling the types and contents of a base resin and a reactant contained in a resin composition for producing a dry film solder resist and thereby reducing chloride ions generated during the production process of the (meth)acrylate-based resin.

[0006] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0007] One embodiment of the present invention provides a (meth)acrylate resin comprising: a first resin comprising repeating units represented by the following chemical formula 1 and the following chemical formula 2; and a second resin comprising repeating units represented by the following chemical formula 3 and the following chemical formula 4.

[0008] [ka] [ka]

[0009] In Chemical Formula 1 to Chemical Formula 4, R1, R2, R3, and R4 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; X is a single bond or O-L1; L1 and L2 each independently represent a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; and * indicates a linking point.

[0010] One embodiment of the present invention provides a resin composition containing the (meth)acrylate resin and an additive. One embodiment of the present invention provides a dry film solder resist comprising the resin composition or a cured product of the resin composition. Effect of the Invention

[0011] The (meth)acrylate resin according to one embodiment of the present invention can reduce the amount of chloride ions generated during the manufacturing process. The (meth)acrylate resin according to one embodiment of the present invention can improve low dielectric constant characteristics. The resin composition according to one embodiment of the present invention has a low content of chloride ions, which can improve insulation reliability and life, suppress the occurrence of migration, and delay the occurrence of migration.

[0012] The dry film solder resist according to an embodiment of the present invention can enhance developability, reduce residues and improve solder adhesion. The dry film solder resist according to an embodiment of the present invention includes an active ester structure, which can improve adhesion to an epoxy molding compound (EMC).In addition, due to the improved adhesion, a process of plasma treating the solder resist before the epoxy molding compound process can be omitted. The effects of the present invention are not limited to those described above, and effects not mentioned will be clearly understood by those skilled in the art from the present specification and the accompanying drawings. [Brief description of the drawings]

[0013] [Figure 1] FIG. 13 is a diagram showing a method for evaluating the adhesion between the surface of a solder resist and an epoxy molding compound in Experimental Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Throughout this specification, when a part is described as "comprising" a certain element, this means that it can further include other elements, but not to the exclusion of other elements, unless specifically stated to the contrary. Throughout this specification, when an element is said to be "on" another element, this includes not only when the element is in contact with the other element, but also when there is another element between the two elements.

[0015] Throughout this specification, the unit "parts by weight" can refer to the weight ratio between each component. Throughout this specification, the unit "molar parts" can refer to the molar ratio between each component. Throughout this specification, "(meth)acrylate" is used generically to refer to acrylate and methacrylate. Throughout this specification, "A and / or B" means "A and B, or A or B."

[0016] Throughout this specification, the term "repeat unit" may refer to the form in which a monomer is reacted in a polymer, specifically, the form in which a monomer undergoes a polymerization reaction to form the backbone of the polymer, for example, the main chain or a side chain.

[0017] Throughout this specification, the "weight average molecular weight" and "number average molecular weight" of a compound are calculated using the molecular weight and molecular weight distribution of the compound. Specifically, a sample specimen with a concentration of 1 wt% of the compound is prepared by putting tetrahydrofuran (THF) and the compound in a 1 ml glass bottle, and a standard sample (polystyrene) and the sample specimen are filtered through a filter (pore size 0.45 μm) and then injected into a GPC injector, and the elution time of the sample specimen is compared with the calibration curve of the standard specimen to obtain the molecular weight and molecular weight distribution of the compound. In this case, an Infinity II 1260 (Agilient) can be used as a measuring instrument, and the flow rate can be set to 1.00 mL / min and the column temperature to 40.0° C.

[0018] Throughout the present specification, the term "glass transition temperature (Tg)" may be measured using Differential Scanning Analysis (DSC). Specifically, a sample is heated at a heating rate of 5°C / min within a temperature range of -60°C to 150°C using a Differential Scanning Calorimeter (DSC-STAR3, METTLER TOLEDO), and two cycles of experiment are performed within the range. The midpoint of the DSC curve is measured at a point where there is a heat change, to determine the glass transition temperature.

[0019] Throughout the present specification, the term "substituted" may mean that a hydrogen atom bonded to a carbon atom of a compound is replaced with another substituent, and the position of the substitution is not limited as long as it is the position of a hydrogen atom, i.e., a position that can be substituted by a substituent, and when two or more substituents are substituted, the two or more substituents may be the same or different.

[0020] Throughout this specification, "substituted or unsubstituted" means that it is substituted with one or more substituents selected from the group consisting of a hydroxy group; an alkyl group; a cycloalkyl group; and an aryl group, or that it is substituted with a substituent in which two or more of the above-listed substituents are linked, or that it has no substituents. For example, the "substituent in which two or more substituents are linked" may be a biphenyl group. That is, the biphenyl group may be an aryl group, and may be interpreted as a substituent in which two phenyl groups are linked.

[0021] Throughout this specification, "alkyl group" can mean straight or branched chain. Throughout this specification, an "alkylene group" can refer to an alkyl group having two points of attachment, ie, a divalent group. Throughout this specification, an "alkenylene group" can refer to an alkene group having two points of attachment, ie, a divalent group. Throughout this specification, "aryl groups" may be monocyclic or polycyclic. Throughout this specification, an "arylene group" can refer to a monocyclic or polycyclic, aryl group having two points of attachment, ie, a divalent group.

[0022] The present invention will now be described in further detail. The acid group-containing (meth)acrylate resin used in conventional dry film solder resist (DFSR) has been manufactured by acrylate of epoxy resin with acrylic acid, followed by reaction with acid anhydride. When manufactured in this manner, the (meth)acrylate resin manufactured contains a large amount of chlorine ions (approximately 800mg / kg or more). Therefore, when the (meth)acrylate resin manufactured by the conventional manufacturing method is applied to a circuit, migration of copper contained in the circuit occurs, which reduces the insulation and induces reliability problems.

[0023] One embodiment of the present invention provides a (meth)acrylate resin comprising: a first resin comprising repeating units represented by the following chemical formula 1 and the following chemical formula 2; and a second resin comprising repeating units represented by the following chemical formula 3 and the following chemical formula 4.

[0024] [ka] [ka]

[0025] In Chemical Formula 1 to Chemical Formula 4, R1, R2, R3, and R4 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; X is a single bond or O-L1; L1 and L2 each independently represent a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; and * indicates a linking point.

[0026] The "alkylene group" can refer to a group that contains a saturated hydrocarbon group attached to the rest of the molecule by two different bonds, the "alkenylene group" can refer to a group that contains a carbon-carbon double bond as an unsaturated hydrocarbon group attached to the rest of the molecule by two different bonds, and the "arylene group" can refer to a group that contains an aromatic ring attached to the rest of the molecule by two different bonds.

[0027] The term "alkyl group" can refer to a group that contains a saturated hydrocarbon group attached to the remainder of the molecule by a single bond, and the term "alkenyl group" can refer to a group that contains a carbon-carbon double bond as an unsaturated hydrocarbon group attached to the remainder of the molecule by a single bond. The term "single bond" means a direct bond, and specifically, when X in Chemical Formula 1 and Chemical Formula 2 is a single bond, benzene and oxygen may be directly bonded to each other.

[0028] The (meth)acrylate resin according to one embodiment of the present invention can reduce chloride ions generated during the manufacturing process and improve low dielectric constant characteristics. In addition, in the acid group-containing (meth)acrylate resin, the acid group serves as a developing group, and the (meth)acrylate resin according to one embodiment of the present specification has an acid group farther away from the main chain than conventional substances, so that it has excellent developability and reduces residues.

[0029] According to one embodiment of the present invention, the (meth)acrylate resin comprises a first resin including repeating units represented by Chemical Formula 1 to Chemical Formula 2, and a second resin including repeating units represented by Chemical Formula 3 and Chemical Formula 4. As described above, by comprising the first resin including repeating units represented by Chemical Formula 1 to Chemical Formula 2, and the second resin including repeating units represented by Chemical Formula 3 and Chemical Formula 4, it is possible to minimize the generation of chloride ions during the production process of the (meth)acrylate resin.

[0030] According to one embodiment of the present invention, the (meth)acrylate resin includes a first resin containing repeating units represented by Chemical Formula 1 and Chemical Formula 2. The (meth)acrylate resin includes repeating units represented by Chemical Formula 1 containing a (meth)acrylate group at an end and Chemical Formula 2 containing a carboxy group at an end. When the (meth)acrylate resin includes a first resin containing repeating units represented by Chemical Formula 1 and Chemical Formula 2, the insulation reliability of a dry film solder resist containing the (meth)acrylate resin can be improved.

[0031] According to one embodiment of the present invention, the (meth)acrylate resin may have a molar ratio of the repeating unit represented by Chemical Formula 1 and the repeating unit represented by Chemical Formula 2 of 9:1 to 1:9. Specifically, the molar ratio of the repeating unit represented by Chemical Formula 1 and the repeating unit represented by Chemical Formula 2 may be 8:2 to 2:8, 7:3 to 3:7, or 6:4 to 4:6. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 1 and the repeating unit represented by Chemical Formula 2 contained in the (meth)acrylate resin within the above-mentioned range, it is possible to minimize the chloride ions generated during the production process of the (meth)acrylate resin.

[0032] According to one embodiment of the present invention, the (meth)acrylate resin may contain 10 to 90 molar parts of the repeating unit represented by Chemical Formula 1 relative to 100 molar parts of the repeating unit of the first resin. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 1 within the above-mentioned range, it is possible to suppress the occurrence of migration and delay the occurrence time.

[0033] According to one embodiment of the present invention, the (meth)acrylate resin may contain 10 to 90 molar parts of the repeating unit represented by Chemical Formula 2 relative to 100 molar parts of the repeating unit of the first resin. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 2 within the above-mentioned range, it is possible to suppress the occurrence of migration and delay the occurrence time.

[0034] According to one embodiment of the present invention, the first resin is ia) a first base resin comprising a repeating unit represented by the following formula 5, or ib) a reaction product of the first base resin with a compound represented by the following formula 6: iia) a compound represented by the following chemical formula 7; or iib) a compound represented by the following chemical formula 8:

[0035] [ka]

[0036] In Chemical Formula 5 to Chemical Formula 8, R1 and R2 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; L1 and L2 each independently represent a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; and * indicates a linking point.

[0037] According to one embodiment of the present invention, the first base resin may be a novolac resin. Specifically, the first base resin may be a cresol novolac resin. When the base resin is a novolac resin, it is possible to minimize the amount of chlorine ions generated during the manufacturing process of the (meth)acrylate resin.

[0038] According to one embodiment of the present invention, the first base resin may have a hydroxyl equivalent of 100 g / eq or more and 150 g / eq or less. According to one embodiment of the present invention, the first resin may contain a hydroxy group derived from the compound represented by Chemical Formula 6 at its terminal. The reaction product of the first base resin and the compound represented by Chemical Formula 6 has a hydroxyl equivalent of 150 g / eq or more and 250 g / eq or less.

[0039] According to one embodiment of the present invention, the compound represented by Chemical Formula 6 may be a carbonate-based compound. More specifically, the compound represented by Chemical Formula 6 may be one selected from the group consisting of methylene carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, pentylene carbonate, and combinations thereof.

[0040] According to one embodiment of the present invention, the first resin may contain a (meth)acrylate group derived from Chemical Formula 7. According to one embodiment of the present invention, the compound represented by Chemical Formula 7 may be an anhydride containing a (meth)acrylate group. According to one embodiment of the present invention, the first resin may contain a carboxy group derived from the compound represented by Chemical Formula 8. According to one embodiment of the present invention, the compound represented by Chemical Formula 8 may include one or more of phthalic anhydride, tetrahydrophthalic anhydride, maleic anhydride, succinic anhydride, and glutaric anhydride.

[0041] According to one embodiment of the present invention, the first resin may be produced by reacting a compound represented by Chemical Formula 7 or a compound represented by Chemical Formula 8 with a hydroxy group of the first base resin or a hydroxy group produced by the reaction of the first base resin with a compound represented by Chemical Formula 6. Specifically, the compound represented by Chemical Formula 6 can form a hydroxy group by ring-opening a cyclic carbonate group contained in the compound, and a compound represented by Chemical Formula 11 is produced by the reaction of the first base resin with the compound represented by Chemical Formula 6. The hydroxy group of the compound represented by Chemical Formula 11 reacts with each of the compound represented by Chemical Formula 7 and the compound represented by Chemical Formula 8 to form a (meth)acrylate and a carboxy group.

[0042] [ka]

[0043] According to one embodiment of the present invention, the first resin may be prepared by reacting 0.5 to 3.0 moles of a compound represented by Chemical Formula 6 with respect to 1 mole of the first base resin.

[0044] According to one embodiment of the present invention, the first resin may be produced by a reaction of 0.1 to 1.5 moles of the compound represented by Chemical Formula 7 relative to 1 mole of the first base resin. Specifically, the compound represented by Chemical Formula 7 may react with a hydroxy group of the first base resin or a terminal hydroxy group produced by a reaction between the first base resin and the compound represented by Chemical Formula 6, or the first resin may be produced by a reaction of 0.1 to 1.5 moles of the compound represented by Chemical Formula 7 relative to 1 mole of the terminal hydroxy group produced by a reaction between the first base resin and the compound represented by Chemical Formula 6.

[0045] According to one embodiment of the present invention, the first resin may be produced by a reaction of 0.1 to 1.0 moles of the compound represented by the chemical formula 8 with respect to 1 mole of the first base resin. Specifically, the compound represented by the chemical formula 8 may react with a hydroxy group of the first base resin or a terminal hydroxy group generated by a reaction between the first base resin and the compound represented by the chemical formula 6, or the first resin may be produced by a reaction of 0.1 to 1.0 moles of the compound represented by the chemical formula 8 with respect to 1 mole of the terminal hydroxy group generated by a reaction between the first base resin and the compound represented by the chemical formula 6. By adjusting the molar ratio of the reaction between the base resin and the compound represented by the chemical formula 8 within the above range, the insulation reliability and life can be improved by a low content of chlorine ions, and the occurrence of migration can be suppressed and the occurrence time can be delayed.

[0046] According to one embodiment of the present invention, the (meth)acrylate resin includes a second resin including repeating units represented by the following chemical formula 3 and the following chemical formula 4. By including repeating units represented by the chemical formula 3 including a hydroxy group and a (meth)acrylate group at the terminals, and the chemical formula 4 including a carboxy group and a (meth)acrylate group at the terminals, the (meth)acrylate resin includes a second resin including repeating units represented by the chemical formula 3 and the chemical formula 4, and thus the insulation reliability of a dry film solder resist including the (meth)acrylate resin can be improved.

[0047] According to one embodiment of the present invention, the (meth)acrylate resin may have a molar ratio of the repeating unit represented by Chemical Formula 3 and the repeating unit represented by Chemical Formula 4 of 9:1 to 1:9. Specifically, the molar ratio of the repeating unit represented by Chemical Formula 3 and the repeating unit represented by Chemical Formula 4 may be 8:2 to 2:8, 7:3 to 3:7, or 6:4 to 4:6. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 3 and the repeating unit represented by Chemical Formula 4 contained in the resin within the above range, it is possible to minimize the chloride ions generated during the production process of the (meth)acrylate resin.

[0048] According to one embodiment of the present invention, the (meth)acrylate resin may contain 10 to 90 molar parts of the repeating unit represented by Chemical Formula 3 relative to 100 molar parts of the repeating unit of the second resin. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 3 within the above-mentioned range, it is possible to suppress the occurrence of migration and delay the occurrence time.

[0049] According to one embodiment of the present invention, the (meth)acrylate resin may contain 10 to 90 molar parts of the repeating unit represented by Chemical Formula 4 relative to 100 molar parts of the repeating unit of the second resin. By adjusting the molar ratio of the repeating unit represented by Chemical Formula 4 within the above-mentioned range, it is possible to suppress the occurrence of migration and delay the occurrence time.

[0050] According to one embodiment of the present invention, the second resin may be prepared by reacting a second base resin including a repeating unit represented by the following formula 9; a compound represented by the following formula 10; and compounds represented by the following formulas 8 and 10.

[0051] [ka]

[0052] In Chemical Formulae 8 to 10, R3 and R4 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; L2 represents a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; and * represents a linking point.

[0053] According to one embodiment of the present invention, the second base resin may be a novolac epoxy resin. Specifically, the second base resin may be a cresol novolac epoxy resin. When the base resin is a novolac epoxy resin, the acid group is located far away from the main chain, thereby exhibiting excellent developability and reduced residue.

[0054] According to one embodiment of the present invention, the second resin may contain a (meth)acrylate group derived from the compound represented by Chemical Formula 10. According to one embodiment of the present invention, the compound represented by Chemical Formula 10 may be a (meth)acrylate acid, or Chemical Formula 10 may be a (meth)acrylate acid remaining as a result of a reaction between the compound represented by Chemical Formula 11, which is a reaction product of the first base resin containing the repeating unit represented by Chemical Formula 5 and the compound represented by Chemical Formula 6, and the compound represented by Chemical Formula 7, during the production process of the first resin.

[0055] According to one embodiment of the present invention, the second resin may contain a carboxy group derived from the compound represented by Chemical Formula 8. According to one embodiment of the present invention, the compound represented by Chemical Formula 8 may include one or more of phthalic anhydride, tetrahydrophthalic anhydride, maleic anhydride, succinic anhydride, and glutaric anhydride.

[0056] According to one embodiment of the present invention, the second resin may be produced by the reaction of the second base resin with the compound represented by Chemical Formula 10, or may be produced by reacting the compound represented by Chemical Formula 8 with a hydroxyl group generated by the reaction of the second base resin with the compound represented by Chemical Formula 10. Specifically, the compound represented by Chemical Formula 3 may form a hydroxyl group by opening a ring contained in the second base resin by the reaction of the second base resin represented by Chemical Formula 9 with the compound represented by Chemical Formula 10. The compound represented by Chemical Formula 4 may form an ester group by reacting a hydroxyl group generated by the reaction of the second base resin with the compound represented by Chemical Formula 10 with one of the carbonyl groups contained in the compound represented by Chemical Formula 8, and the remaining carboxyl group contained in the compound may become a carboxyl group of the resin.

[0057] According to one embodiment of the present invention, the second resin may be produced by a reaction of 0.5 to 1.5 moles of the compound represented by Chemical Formula 10 relative to 1 mole of the second base resin. Specifically, the second resin may be produced by a reaction of 0.5 to 1.5 moles of the compound represented by Chemical Formula 10 relative to 1 mole of the epoxy group of the second base resin.

[0058] According to one embodiment of the present invention, the second resin may be produced by a reaction of 0.1 to 1.0 moles of the compound represented by the chemical formula 8 with respect to 1 mole of the second base resin. Specifically, the second base resin reacts with the compound represented by the chemical formula 10 to form a hydroxyl group, and the hydroxyl group reacts with the compound represented by the chemical formula 8, and the number of moles of the hydroxyl group formed by the reaction of the second base resin with the compound represented by the chemical formula 10 may be the same as the number of moles of the epoxy group of the second base resin. Therefore, the second resin may be produced by a reaction of 0.1 to 1.5 moles of the compound represented by the chemical formula 8 with respect to 1 mole of the hydroxyl group generated by the reaction of the second base resin with the compound represented by the chemical formula 10. Specifically, the second resin may be produced by a reaction of 0.2 to 0.9 moles, 0.3 to 0.8 moles, 0.4 to 0.7 moles, or 0.5 to 0.6 moles of the compound represented by the chemical formula 8 with respect to 1 mole of the epoxy group of the base resin. By adjusting the molar ratio of the reaction between the second base resin and the compound represented by Formula 8 within the above range, it is possible to improve the developability and the low dielectric constant.

[0059] According to one embodiment of the present invention, the first resin is ia) a first base resin including a repeating unit represented by the following chemical formula 5, or ib) a reaction product of the first base resin and a compound represented by the following chemical formula 6, with iia) a compound represented by the following chemical formula 7, or iib) a compound represented by the following chemical formula 8. The second resin may be produced by a reaction of ic) a second base resin including a repeating unit represented by the following chemical formula 9, with iic) a compound represented by the following chemical formula 10, or iid) a compound represented by the following chemical formula 10 and a compound represented by the following chemical formula 8.

[0060] [ka] [ka]

[0061] In Chemical Formula 5 to Chemical Formula 10, each of R1 to R4 independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; each of L1 and L2 independently represents a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; and * indicates a linking point.

[0062] As described above, by preparing the first resin and the second resin, the content of chloride ions in the composition can be reduced, and the acid groups can be located far away from the main chain, which provides excellent developability and reduces residues.

[0063] One embodiment of the present invention provides a resin composition comprising a (meth)acrylate resin and an additive. The resin composition according to one embodiment of the present invention has a low content of chloride ions, which can improve insulation reliability and life, suppress the occurrence of migration, and delay the occurrence of migration. According to one embodiment of the present invention, the additive may include one or more of a photoinitiator, a thermosetting binder, an inorganic filler, a dispersant, a thermosetting binder catalyst, a pigment, a photocurable monomer, an ion scavenger, an antioxidant, and a filler.

[0064] According to one embodiment of the present invention, the additives include 1 to 10 kinds of a photoinitiator, a thermosetting binder, an inorganic filler, a dispersant, a thermosetting binder catalyst, a pigment, a photocurable monomer, an ion scavenger, an antioxidant, and a filler. Specifically, the additives may include 2 to 8 kinds. According to one embodiment of the present invention, the photoinitiator may be one that initiates radical photocuring of the resin composition in exposed areas.

[0065] According to one embodiment of the present invention, the photoinitiator may be benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-t-butyldioxy-1-methylethyl)acetophenone; anthraquinones such as 2-methylanthraquinone, 2-amylanthraquinone, 2-t-butylanthraquinone, and 1-chloroanthraquinone; thioxanthones such as 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; and benzophenones such as benzophenone, 4-(1-t-butyldioxy-1-methylethyl)benzophenone, and 3,3',4,4'-tetrakis(t-butyldioxycarbonyl)benzophenone. In addition, examples of photoinitiators include α-aminoacetophenones such as 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropanone-1,2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, and N,N-dimethylaminoacetophenone; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Materials such as sphingoside oxides, acylphosphine oxides such as bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide; and oxime esters such as 2-(acetyloxyiminomethyl)thioxanthen-9-one, (1,2-octanedione, 1-[4-(phenylthio)phenyl]-, 2-(O-benzoyloxime)), (ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime)), can be used.More specifically, examples of photoinitiators that can be used include commercially available products from Ciba Specialty Chemicals (now Ciba Japan) such as Irgacure (registered trademark) 907, Irgacure 369, Irgacure 379, Irgacure 819, Irgacure 2100, GGI-325, Irgacure OXE01, Irgacure OXE02, and Darocur TPO; Lucirin (registered trademark) TPO from BASF; and N-1919 from ADEKA. The above-mentioned commercially available products may be included in the above-mentioned photoinitiator substances (α-aminoacetophenones, oxime esters, etc.).

[0066] According to one embodiment of the present invention, the content of the photoinitiator may be 0.5% by weight to 20% by weight, specifically 1% by weight to 10% by weight, more specifically 1% by weight to 5% by weight, based on the total weight of the solid content of the resin composition. The solid content of the resin composition means the portion of the resin composition that takes into account only the components excluding the solvent and volatile matter.

[0067] According to one embodiment of the present invention, the content of the photoinitiator may be 0.1 to 20 parts by weight, specifically 0.1 to 10 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. By adjusting the content of the photoinitiator within the above-mentioned range, it is possible to prevent the content of the photoinitiator being less than the exemplified content, which causes photocuring to not occur properly, and to prevent the content of the photoinitiator being more than the exemplified content, which causes the resolution of the resin composition to decrease or the reliability of DFSR to become insufficient.

[0068] According to one embodiment of the present invention, the thermosetting binder contains a thermosetting functional group. For example, the thermosetting binder contains at least one selected from the group consisting of an epoxy group, an oxetanyl group, a cyclic ether group, and a cyclic thioether group. Such a thermosetting binder can improve the heat resistance or mechanical properties of the DFSR by forming a crosslink with the (meth)acrylate resin through thermal curing.

[0069] According to one embodiment of the present invention, the thermosetting binder can be a resin having two or more cyclic ether groups and / or cyclic thioether groups (hereinafter referred to as cyclic (thio)ether groups) in the molecule; other diisocyanates and their bifunctional blocked isocyanates; polyfunctional epoxy compounds having at least two or more epoxy groups in the molecule; polyfunctional oxetane compounds having at least two or more oxetanyl groups in the molecule; and / or compounds having two or more thioether groups in the molecule.

[0070] The thermosetting binder having two or more cyclic (thio)ether groups in the molecule may be a compound having two or more of either one or both of a 3-, 4- or 5-membered cyclic ether group or a cyclic thioether group in the molecule.

[0071] The compound having two or more cyclic thioether groups in the molecule may be an episulfide resin. Examples of the compound having two or more cyclic thioether groups in the molecule include bisphenol A episulfide resin YL7000 manufactured by Japan Epoxy Resin Co., Ltd. Also, episulfide resins in which the oxygen atom of the epoxy group of a novolac epoxy resin is replaced with a sulfur atom can be used.

[0072] Examples of the polyfunctional epoxy compound include bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, brominated bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, N-glycidyl type epoxy resin, bisphenol A novolac type epoxy resin, bixylenol type epoxy resin, biphenol type epoxy resin, chelate type epoxy resin, glyoxal type epoxy resin, amino group-containing epoxy resin, rubber-modified epoxy resin, dicyclopentadiene phenolic type epoxy resin, diglycidyl phthalate resin, heterocyclic epoxy resin, tetraglycidyl xylenoyl ethane resin, silicone-modified epoxy resin, ε-caprolactone-modified epoxy resin, etc. In addition, in order to impart flame retardancy, atoms such as phosphorus may be introduced into the structure. These epoxy resins are thermally cured to improve properties such as adhesion of the cured coating, solder heat resistance, and electroless plating resistance.

[0073] According to one embodiment of the present invention, examples of the polyfunctional oxetane compound include bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, (3-ethyl-3-oxetanyl)methyl Examples of the oxetanes include polyfunctional oxetanes such as ethyl acrylate, (3-methyl-3-oxetanyl)methyl methacrylate, (3-ethyl-3-oxetanyl)methyl methacrylate, and oligomers or copolymers thereof, as well as ethers of oxetane alcohols with novolac resins, poly(p-hydroxystyrene), cardo-type bisphenols, calixarenes, calixresorcinarenes, or resins having hydroxyl groups such as silsesquioxane. Other examples include copolymers of unsaturated monomers having an oxetane ring and alkyl (meth)acrylates.

[0074] As the thermosetting binder, commercially available products such as YDCN-500-80P and YDCN-500-90P manufactured by Kukdo Chemical Co., Ltd. can be used.

[0075] According to one embodiment of the present invention, the content of the thermosetting binder may be 5 parts by weight to 50 parts by weight, specifically 10 parts by weight to 30 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. If the content of the thermosetting binder is less than the exemplified content, carboxyl groups may remain in the DFSR after curing, resulting in a decrease in heat resistance, alkali resistance, electrical insulation, etc., whereas if the content is more than the exemplified content, the strength of the film may decrease due to the remaining thermosetting binder, which is not preferable. According to one embodiment of the present invention, the thermosetting binder catalyst may be adapted to accelerate the thermal curing of a thermosetting binder.

[0076] According to one embodiment of the present invention, the thermosetting binder catalyst may be selected from the group consisting of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide, sebacic acid dihydrazide; phosphorus compounds such as triphenylphosphine; and S-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-4,6-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine-isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-S-triazine-isocyanuric acid adduct, etc., can be used.

[0077] Specifically, examples of the thermosetting binder catalyst that can be used include commercially available products manufactured by Shikoku Chemical Industry Co., Ltd., such as 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, and 2P4MHZ (trade names of imidazole-based compounds), and products manufactured by San-Apro Co., Ltd., such as U-CAT3503N, UCAT3502T (trade names of dimethylamine blocked isocyanate compounds), DBU, DBN, U-CATS A102, and U-CAT5002 (bicyclic amidine compounds and salts thereof).

[0078] According to one embodiment of the present invention, the thermosetting binder catalyst may be a thermosetting catalyst of an epoxy resin or an oxetane compound; a catalyst that promotes the reaction of an epoxy group and / or an oxetanyl group with a carboxy group, etc., and the above-mentioned substances may be used alone or in combination of two or more kinds. In addition, a compound that also functions as an adhesion imparting agent may be used in combination with the thermosetting binder catalyst.

[0079] According to one embodiment of the present invention, the content of the thermosetting binder catalyst may be 0.3% by weight to 2% by weight based on the solid content of the resin composition. According to one embodiment of the present invention, the content of the thermosetting binder catalyst may be 0 to 20 parts by weight, specifically 0.1 to 10 parts by weight, relative to 100 parts by weight of the (meth)acrylate resin.

[0080] According to one embodiment of the present invention, the inorganic filler serves to improve the heat resistance, dimensional stability under heat, and resin adhesion of the produced DFSR, and also serves as an extender pigment by reinforcing the color. According to one embodiment of the present invention, the inorganic filler may be a plate-like inorganic filler or a spherical silica filler. According to one embodiment of the present invention, the content of the inorganic filler may be 40% by weight to 80% by weight, specifically 60% by weight to 70% by weight, based on the solid content of the resin composition.

[0081] According to one embodiment of the present invention, the content of the inorganic filler may be 50 parts by weight to 1,000 parts by weight, specifically 100 parts by weight to 500 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. If the content of the inorganic filler is more than the exemplified content, the viscosity of the composition increases, which is undesirable because the coating property decreases or the degree of curing decreases. Also, if the content of the inorganic filler is less than the exemplified content, the modulus improvement effect cannot be expected, and the developability and thermal expansion coefficient may decrease.

[0082] According to one embodiment of the present invention, the dispersant is used to improve the dispersion stability of fillers, pigments, etc. contained in the composition, and the use of the dispersant makes it possible to easily form a fine pattern. According to one embodiment of the present invention, the dispersant may be Tyzor AA, AA-65, AA-105, etc., manufactured by Dorf Ketal.

[0083] According to one embodiment of the present invention, the content of the dispersant is preferably 1% by weight to 6% by weight based on the total weight of the solid content of the resin composition. If the amount of the dispersant added is too small, less than 1% by weight, dispersion is insufficient, which is disadvantageous for the formation of fine patterns, and if it exceeds 6% by weight, it may affect heat resistance and reliability.

[0084] According to one embodiment of the present invention, the pigment provides visibility and hiding power to hide defects such as scratches in circuit lines.

[0085] According to one embodiment of the present invention, the pigment may be red, blue, green, yellow, or black. For example, phthalocyanine blue, pigment blue, pigment green, solvent green, and / or pigment yellow may be used. Specifically, the blue pigment may be phthalocyanine blue, pigment blue 15:1, pigment blue 15:2, pigment blue 15:3, pigment blue 15:4, pigment blue 15:6, or pigment blue 60. The green pigment may be pigment green 7, pigment green 36, solvent green 3, solvent green 5, solvent green 20, or solvent green 28. Yellow pigments include anthraquinone-based, isoindolinone-based, condensed azo-based, and benzimidazolone-based pigments. For example, Pigment Yellow 108, Pigment Yellow 147, Pigment Yellow 151, Pigment Yellow 166, Pigment Yellow 181, and Pigment Yellow 193 can be used.

[0086] According to one embodiment of the present invention, the content of the pigment may be 0.5% by weight to 3% by weight based on the solid content of the resin composition. According to one embodiment of the present invention, the content of the pigment may be 0.1 to 20 parts by weight, specifically 0.1 to 10 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. If the content of the pigment is less than the exemplified content, the visibility and hiding power are reduced, and if the content of the pigment is more than the exemplified content, the heat resistance is reduced.

[0087] According to one embodiment of the present invention, the photocurable monomer can form a crosslink with the unsaturated functional group of the (meth)acrylate resin to form a crosslinked structure by photocuring during exposure. This allows the resin composition in the exposed area corresponding to the area where DFSR is formed to remain on the substrate without being developed by alkali. In addition, the photocurable monomer can be liquid at room temperature, and can also play a role in adjusting the viscosity of the resin composition according to the application method and further improving the alkali developability of the non-exposed area.

[0088] According to one embodiment of the present invention, the photocurable monomer may be a compound having a photocurable unsaturated functional group such as a multifunctional vinyl group.

[0089] According to one embodiment of the present invention, the photocurable monomer may be an acrylate-based compound having two or more photocurable unsaturated functional groups. For example, acrylate-based compounds containing a hydroxyl group, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, pentaerythritol triacrylate, or dipentaerythritol pentaacrylate; water-soluble acrylate-based compounds, such as polyethylene glycol diacrylate or polypropylene glycol diacrylate; polyfunctional polyester acrylate-based compounds, such as trimethylolpropane triacrylate, pentaerythritol tetraacrylate, or dipentaerythritol hexaacrylate; ethylene oxide adducts of polyfunctional alcohols, such as trimethylolpropane and hydrogenated bisphenol A, or polyhydric phenols, such as bisphenol A and biphenol. and / or acrylate compounds which are propylene oxide adducts; polyfunctional or monofunctional polyurethane acrylate compounds which are isocyanate modified hydroxyl group-containing acrylates; epoxy acrylate compounds which are (meth)acrylic acid adducts of bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, or phenol novolac epoxy resin; and / or caprolactone modified acrylate compounds such as caprolactone modified ditrimethylolpropane tetraacrylate, ε-caprolactone modified dipentaerythritol acrylate, or caprolactone modified hydroxypivalic acid neopentyl glycol ester diacrylate. The above-mentioned compounds may be used alone or in combination of two or more.

[0090] According to one embodiment of the present invention, among these, a polyfunctional (meth)acrylate compound having two or more (meth)acryloyl groups in the molecule can be used as the photocurable monomer. In particular, pentaerythritol triacrylate, trimethylolpropane triacrylate (TMPTA), dipentaerythritol hexaacrylate (DPHA), caprolactone-modified ditrimethylolpropane tetraacrylate, etc. can be appropriately used.

[0091] According to one embodiment of the present invention, the content of the photocurable monomer may be 1 wt % to 30 wt %, or 2 wt % to 20 wt %, based on the total weight of the resin composition.

[0092] According to one embodiment of the present invention, the content of the photocurable monomer may be 1 to 40 parts by weight, specifically 5 to 30 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. If the content of the photocurable monomer is less than the exemplified content, photocuring may be insufficient, and if the content is more than the exemplified content, the drying property of DFSR may be poor, and the physical properties may be deteriorated. According to one embodiment of the present invention, the solvent may be a mixture of one or more solvents in order to dissolve the resin composition or to impart an appropriate viscosity to the resin composition.

[0093] According to one embodiment of the present invention, the solvent may be a ketone such as methyl ethyl ketone (MEK) or cyclohexanone; an aromatic hydrocarbon such as toluene, xylene or tetramethylbenzene; a glycol ether (cellosolve) such as ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol diethyl ether or triethylene glycol monoethyl ether; ethyl acetate, Examples of the solvent include acetates such as butyl acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, and dipropylene glycol monomethyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, propylene glycol, and carbitol; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha; and amides such as dimethylacetamide and dimethylformamide (DMF). These solvents can be used alone or as a mixture of two or more of them.

[0094] According to one embodiment of the present invention, the content of the solvent may be about 1% by weight to 50% by weight based on the total weight of the resin composition. According to one embodiment of the present invention, the content of the solvent may be 0.5 to 40 parts by weight, specifically 0.5 to 20 parts by weight, based on 100 parts by weight of the (meth)acrylate resin. If the content of the solvent is less than the exemplified content, the viscosity is high and the coating property is reduced, and if the content exceeds the exemplified content, drying is not performed well and stickiness increases.

[0095] According to one embodiment of the present invention, the ion scavenger and antioxidant can be any material used in the art without any restrictions. According to one embodiment of the present invention, the filler may be an organic or inorganic filler, such as barium sulfate, barium titanate, amorphous silica, crystalline silica, fused silica, spherical silica, clay, magnesium carbonate, calcium carbonate, aluminum oxide (alumina), aluminum hydroxide, mica, or the like.

[0096] One embodiment of the present invention provides a dry film solder resist comprising the resin composition or a cured product of the resin composition. The dry film solder resist according to an embodiment of the present invention can enhance developability, reduce residues and improve solder adhesion. In one embodiment of the present invention, the process for preparing the dry film solder resist is the same as that used in the art, except that the above-mentioned resin composition is used. For example, the dry film solder resist can be prepared by the following method.

[0097] First, the resin composition is applied as a photosensitive coating material to a carrier film using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, or the like, and then the film is dried in an oven at a temperature of 50°C to 130°C for 1 to 30 minutes. Then, a release film is laminated on the film to produce a dry film composed of a carrier film, a photosensitive film, and a release film from the bottom. In one embodiment of the present invention, the photosensitive film may have a thickness of about 5 μm to 100 μm.

[0098] In one embodiment of the present invention, the carrier film may be a plastic film such as polyethylene terephthalate (PET), polyester film, polyimide film, polyamideimide film, polypropylene film, polystyrene film, etc., and the release film may be polyethylene (PE), polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc. When the release film is peeled off, it is preferable that the adhesive strength between the photosensitive film and the release film is lower than the adhesive strength between the photosensitive film and the carrier film.

[0099] Next, after removing the release film, a photosensitive film layer is bonded onto the substrate on which the circuit has been formed, using a vacuum laminator, a hot roll laminator, a vacuum press, or the like. Next, the substrate is exposed to light (such as UV) having a certain wavelength range. The exposure may be selectively performed using a photomask, or may be directly pattern-exposed using a laser direct exposure machine. The carrier film is peeled off after exposure. The exposure amount varies depending on the thickness of the coating film, but is generally 0 mJ / cm2. 2 ~1,000mJ / cm 2 When the exposure is allowed to proceed, for example, in the exposed area, photocuring occurs and crosslinks are formed between the unsaturated functional groups, resulting in a state in which the unsaturated functional groups are not removed by subsequent development. In contrast, in the non-exposed area, the crosslinks and the resulting crosslinked structures are not formed, and the carboxyl groups are maintained, resulting in an alkali developable state.

[0100] Next, development is performed using an alkaline solution. The alkaline solution may be an aqueous solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. This type of development allows only the exposed area of ​​the film to remain.

[0101] Finally, the printed circuit board including the solder resist formed from the photosensitive film is completed by heat curing (Post Cure). The heat curing temperature is suitably 100°C or higher.

[0102] One embodiment of the present invention provides a circuit board comprising the dry film solder resist. In one embodiment of the present invention, the circuit board may be formed using various conventional techniques without any limitations, except for the dry film solder resist. In one embodiment of the present invention, the circuit board is a semiconductor circuit board.

[0103] According to one embodiment of the present invention, the (meth)acrylate resin can react with an epoxy molding compound (EMC) by including a first resin including repeating units represented by Chemical Formula 1 to Chemical Formula 2 and a second resin including repeating units represented by Chemical Formula 3 and Chemical Formula 4. The (meth)acrylate resin of the present invention includes an active ester structure represented by Chemical Formula 1 to Chemical Formula 4, and the epoxy molding compound includes an epoxy structure, so that the active ester group can react with an epoxy group as shown in the following reaction formula 1. The reaction occurs under a base condition such as DMAP, and occurs under general organic reaction temperature (25° C.) and pressure (1 atm) conditions, and can also occur under high temperature, high pressure, or high temperature and high pressure conditions.

[0104] According to one embodiment of the present invention, the active ester group of the dry film solder resist reacts with the epoxy group of the epoxy molding compound to increase the adhesion between the dry film solder resist and the epoxy molding compound. Most of the reliability problems occurring in semiconductor packages to which a substrate is applied occur at the interface between the solder resist and the epoxy molding compound, or between an adhesive and the solder resist. Generally, a plasma treatment is performed on the solder resist to increase the adhesion between the solder resist and the epoxy molding compound, but the solder resist containing the resin having the active ester group of the present invention can increase the adhesion to the epoxy molding compound without the plasma treatment.

[0105] [ka] According to one embodiment of the present invention, the adhesion between the dry film solder resist and the epoxy molding compound is 10 kgf / cm 2 ~100Kgf / cm 2 Specifically, the adhesion strength may be 15 kgf / cm 2 ~80Kgf / cm 2 , 15Kgf / cm 2 ~60Kgf / cm 2 , 15Kgf / cm 2 ~40Kgf / cm 2 , or 15 kgf / cm 2 ~35Kgf / cm 2 may be also possible. EXAMPLES

[0106] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various different forms, and the scope of the present invention is not to be construed as being limited to the examples described below. The examples in the present specification are provided to more completely explain the present invention to those having average knowledge in the art.

[0107] Production of (meth)acrylate resins Manufacturing Example 1 122g of cresol novolac resin (Nanokor NPS-9113), 88g of ethylene carbonate (1 equivalent to the cresol novolac resin), 7.89g of triphenylphosphine, and 420g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 200°C for 4 hours while blowing in air and stirring. Then, 154g of methacrylate anhydride (1 equivalent to the cresol novolac resin) and 218g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 1 equivalent to the cresol novolac resin) were added to the resulting reaction product, and the mixture was reacted at 98°C for 16 hours. Next, 60g of tetrahydrophthalic anhydride (0.4 equivalent to the cresol novolac resin) was added, and the reaction was allowed to proceed at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 60%.

[0108] Manufacturing Example 2 122g of cresol novolac resin (Nanokor NPS-9113), 88g of ethylene carbonate (1 equivalent to the cresol novolac resin), 7.89g of triphenylphosphine and 480g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 200°C for 4 hours while blowing in air and stirring. Then, 154g of methacrylate anhydride (1 equivalent to the cresol novolac resin) and 218g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 1 equivalent to the cresol novolac resin) were added to the reaction product obtained, and the mixture was reacted at 98°C for 16 hours. Next, 91g of tetrahydrophthalic anhydride (0.6 equivalent to the cresol novolac resin) was added, and the reaction was carried out at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 60%.

[0109] Production Example 3 122g of cresol novolac resin (Nanokor NPS-9113), 176g of ethylene carbonate (2 equivalents relative to the cresol novolac resin), 7.89g of triphenylphosphine, and 500g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 200°C for 4 hours while blowing in air and stirring. Then, 154g of methacrylate anhydride (1 equivalent relative to the cresol novolac resin) and 218g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 1 equivalent relative to the cresol novolac resin) were added to the reaction product, and the mixture was reacted at 98°C for 16 hours. Next, 91g of tetrahydrophthalic anhydride (0.6 equivalents relative to the cresol novolac resin) was added, and the reaction was carried out at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 60%.

[0110] Production Example 4 122g of cresol novolac resin (Nanokor NPS-9113), 88g of ethylene carbonate (1 equivalent to the cresol novolac resin), 7.89g of triphenylphosphine, and 360g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 200°C for 4 hours while blowing in air and stirring. Then, 123g of methacrylate anhydride (0.8 equivalent to the cresol novolac resin) and 174g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 0.8 equivalent to the cresol novolac resin) were added to the resulting reaction product, and the mixture was reacted at 98°C for 16 hours. Next, 36g of tetrahydrophthalic anhydride (0.24 equivalent to the cresol novolac resin) was added, and the reaction was allowed to proceed at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 60%.

[0111] Production Example 5 122g of cresol novolac resin (Nanokor NPS-9113), 88g of ethylene carbonate (1 equivalent to the cresol novolac resin), 7.89g of triphenylphosphine, and 310g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 98°C for 4 hours while blowing in air and stirring. Then, 92g of methacrylate anhydride (0.6 equivalent to the cresol novolac resin) and 130g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 0.6 equivalent to the cresol novolac resin) were added to the reaction product, and the mixture was reacted at 200°C for 16 hours. Next, 36g of tetrahydrophthalic anhydride (0.24 equivalent to the cresol novolac resin) was added, and the reaction was carried out at 85°C for 8 hours to produce a (meth)acrylate resin with a solid content of 60%.

[0112] Production Example 6 122g of cresol novolac resin (Nanokor NPS-9113), 88g of ethylene carbonate (1 equivalent to the cresol novolac resin), 7.89g of triphenylphosphine and 250g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added, and the mixture was reacted at 200°C for 4 hours while blowing in air and stirring. Then, 61g of methacrylate anhydride (0.4 equivalent to the cresol novolac resin) and 87g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 0.4 equivalent to the cresol novolac resin) were added to the reaction product, and the mixture was reacted at 98°C for 16 hours. Next, 24g of tetrahydrophthalic anhydride (0.16 equivalent to the cresol novolac resin) was added, and the reaction was carried out at 85°C for 8 hours to produce a (meth)acrylate resin with a solid content of 60%.

[0113] Production Example 7 400g of cresol novolac resin (Nanokor NPS-9113), 250g of methacrylate anhydride (0.5 equivalents relative to the cresol novolac resin), and 320g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 0.5 equivalents relative to the cresol novolac resin) were added, and then 20g of triphenylphosphine and 1200g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added and reacted at 98°C for 16 hours. Next, 262g of glutaric anhydride (0.7 equivalents relative to the cresol novolac resin) was added, and the reaction was carried out at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 51%.

[0114] Production Example 8 400g of cresol novolac resin (Nanokor NPS-9113), 250g of methacrylate anhydride (0.5 equivalents relative to the cresol novolac resin) and 320g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P, 0.5 equivalents relative to the cresol novolac resin) were added, and 20g of triphenylphosphine and 1200g of propylene glycol monomethyl ether acetate (PGMEA) solvent were added and reacted at 98°C for 16 hours. Next, 187g of glutaric anhydride (0.5 equivalents relative to the cresol novolac resin) was added and the reaction was allowed to proceed at 85°C for 8 hours. Next, 100g of tetrahydrophthalic anhydride (0.2 equivalents relative to the cresol novolac resin) was added and the reaction was allowed to proceed at 85°C for 8 hours to produce a (meth)acrylate-based resin with a solid content of 51%.

[0115] Comparative Manufacturing Example 1 205g of cresol novolac epoxy resin (Kukdo Chemical YDCN-500-90P), 72g of acrylic acid (1 equivalent to the cresol novolac epoxy resin), 2.6g of triphenylphosphine and 225g of PGMEA solvent were added, and the mixture was reacted at 98°C for 4 hours while blowing in nitrogen and stirring. Then, 61g of tetrahydrophthalic anhydride (0.4 equivalent to the cresol novolac epoxy resin) was added to the resulting compound, and the reaction was allowed to proceed at 85°C for 8 hours to produce a (meth)acrylate resin with a solid content of 60%.

[0116] Experimental Example 1 (Measurement of Chloride Ion Content) The resin solutions prepared in the above Preparation Examples and Comparative Preparation Examples were quantitatively analyzed for chloride ion content using a C-IC device. The measured chloride ion content based on the solid content is shown in Table 1 below.

[0117] [Table 1] It can be seen from Table 1 that the (meth)acrylate resins prepared in Preparation Examples 1 to 8 have a lower Cl ion content than the (meth)acrylate resin prepared in Comparative Preparation Example 1.

[0118] Dry film solder resist manufacturing The resin compositions shown in Table 2 below were prepared.

[0119] [Table 2] *Pigment: Pigment blue and Pigment yellow 5:5 by weight, *Photocurable monomer: DPHA, thermosetting binder: YDCN-500-90P 75% in MEK *Thermosetting binder catalyst: Melamine *Photoinitiator: Irgacure2100 *Solvent: MEK

[0120] The prepared resin composition was applied onto a PET film using a comma coater, and then dried in an oven at 90°C for 3 minutes to obtain a photosensitive film with a thickness of 15 μm. A release film was laminated on the prepared film to prepare a dry film solder resist consisting of a carrier film (PET film), a photosensitive film, and a release film in that order.

[0121] Experimental Example 2 (Developability Evaluation) A copper foil laminate LG-T-500GA (thickness of copper foil laminate: 0.1 mm, thickness of copper foil: 12 μm, product name, manufactured by LG Chemical) was chemically etched to form a micro-roughness on the surface of the copper foil. After removing the release film from the dry film produced on the substrate by the above-mentioned method, the substrate was vacuum laminated using a vacuum laminator (MV LP-500 manufactured by Meiki Seisakusho Co., Ltd.). After drying in an oven at 80°C for 30 minutes, the PET film was removed and the specimen was placed in a Na 2 CO 3 After developing for a certain period of time in a 1% by weight alkaline solution, the substrate was visually judged according to the following criteria as to whether the development was complete. ○: The developed side shows the same color as the uncovered side of the film. X: The developed side shows a color difference from the uncovered side of the film.

[0122] Experimental Example 3 (Residue Evaluation) LG-T-500GA copper foil laminate was chemically etched to create a micro-roughness on the surface of the copper foil. After removing the release film from the dry film produced on the substrate by the above-mentioned method, the substrate was vacuum laminated using a vacuum laminator (MV LP-500 manufactured by Meiki Seisakusho Co., Ltd.). The substrate prepared as described above was exposed to a photomask and irradiated with UV light of 365 nm wavelength at 350 mJ / cm 2 After that, the PET film was removed and the film was placed in a Na 2 CO 3 The film was developed with a 1 wt % alkaline solution for a certain period of time to form a pattern. The inside of 80 μm SRO (solder resist open) was observed using a SEM to see if silica was present on the surface, and was evaluated according to the following criteria. ◎:0 pieces ○:1~5 pieces △:5~10 pieces X: Exceeding 10 pieces

[0123] Experimental Example 4 (Bias HAST resistance evaluation) The copper surface of the LG-T-500GA copper foil laminate, a substrate for printed wiring boards in which copper foil is laminated onto a glass epoxy base material, was etched to form electrodes with a line / space of 30 μm / 30 μm. This substrate was used as an evaluation substrate, and the entire area of ​​the substrate was irradiated with 350 mJ / cm without a photomask. 2 A cured resist was formed in the same manner as in preparing the test piece for residue evaluation measurement in Experimental Example 3, except that the exposure was performed at an exposure dose of 1000 nm. Thereafter, a voltage was applied for 300 hours under conditions of 130° C., 85% RH, and 5 V, and the resist was evaluated according to the following criteria. ◎: 300 hours or more ○: 168 hours or more but less than 300 hours △: 96 hours or more but less than 168 hours X: Less than 96 hours

[0124] Experimental Example 5 (Dielectric Properties Evaluation) The dry films of 15 cm×15 cm size obtained in the above examples and comparative examples were laminated on copper foil of 16 cm×16 cm size, and then the entire area was exposed to 400 mJ / cm without a photomask. 2 Except for the exposure at an exposure dose of 1000 nm, the same procedures were carried out up to heat curing in the same manner as in the preparation of test pieces for measuring moisture absorption and heat resistance in Experimental Example 4, and only the copper foil was etched to prepare a DFSR test piece (cured film). The dielectric constant of the cured film was measured in a 10 GHz band using a Vector Network Analyzer manufactured by Agilent Technologies as a measuring instrument and a Split Post Dieletric Resonator manufactured by QWED as a measuring jig.

[0125] Experimental Example 6 (Adhesion Evaluation) The adhesion between the surface of the solder resist prepared from the solder resist composition obtained in the Examples and Comparative Examples and the epoxy molding compound was measured by a shear test method. Specifically, in Examples 1 to 8, the surface of the solder resist was not plasma-treated, but instead, an epoxy molding compound was molded on the surface of the solder resist, and cured to prepare a cylindrical measurement sample with a size of 3×3.3×2.8 mm, as shown in Fig. 1. After the measurement samples were subjected to PCT, a shear test was performed on 10 samples to confirm the average value of the adhesion between the surface of the solder resist and the epoxy molding compound. In Comparative Example 1, the adhesion between the surface of the solder resist and the epoxy molding compound was measured in the same manner as in the above-mentioned Examples. Table 3 below shows the experimental results measured in Experimental Examples 2 to 6.

[0126] [Table 3]

[0127] From Table 3, it can be seen that the films prepared in Examples 1 to 8 are all excellent in developability, silica residue, bias HAST resistance, dielectric constant and adhesion, whereas the film prepared in Comparative Example 1 is all poor in developability, silica residue, bias HAST resistance and adhesion.

[0128] As a result, it was confirmed that the (meth)acrylate resin according to one embodiment of the present invention has a reduced chloride ion content during the manufacturing process, which reduces the occurrence of copper migration and improves bias HAST resistance. Although the present invention has been described above using a limited number of examples, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims described below.

Claims

1. A (meth)acrylate-based resin comprising: a first resin including repeating units represented by the following Chemical Formula 1 and the following Chemical Formula 2; and a second resin including repeating units represented by the following Chemical Formula 3 and the following Chemical Formula 4: 【Chemistry 1A】 【Chemistry 1B】 In the above Chemical Formula 1 to Chemical Formula 4, R1, R2, R3, and R4 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; X is a single bond or O-L1; each of L1 and L2 independently represents a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; * indicates a connection point.

2. The first resin is ia) a first base resin comprising a repeating unit represented by the following formula 5; or ib) a reaction product of the first base resin and a compound represented by the following formula 6: iia) a compound represented by the following chemical formula 7; or iib) a compound represented by the following chemical formula 8: 【Chemistry 2】 In the above Chemical Formula 5 to Chemical Formula 8, R1 and R2 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; each of L1 and L2 independently represents a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; * indicates a connection point.

3. The (meth)acrylate resin according to claim 2 , wherein the first resin is produced by a reaction of 0.5 to 3.0 moles of the compound represented by Chemical Formula 6 with respect to 1 mole of the first base resin.

4. The (meth)acrylate resin according to claim 2 , wherein the first base resin has a hydroxyl equivalent of 100 g / eq or more and 150 g / eq or less.

5. The (meth)acrylate resin according to claim 2 , wherein a hydroxyl equivalent of the reaction product of the first base resin and the compound represented by Chemical Formula 6 is 150 g / eq or more and 250 g / eq or less.

6. The (meth)acrylate resin according to claim 2 , wherein the first resin is produced by a reaction of 0.1 to 1.5 moles of the compound represented by Chemical Formula 7 with respect to 1 mole of the first base resin.

7. The (meth)acrylate resin according to claim 2 , wherein the first resin is produced by a reaction of 0.1 mol to 1.0 mol of the compound represented by Chemical Formula 8 relative to 1 mol of the first base resin.

8. The second resin is ic) a second base resin including a repeating unit represented by the following formula 9; and iic) a compound represented by the following chemical formula 10; or iid) a compound represented by the following chemical formula 10 and a compound represented by the following chemical formula 8: 【Chemistry 3】 In the above Chemical Formula 8 to Chemical Formula 10, R3 and R4 each independently represent a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; L2 is a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; * indicates a connection point.

9. The (meth)acrylate resin according to claim 8, wherein the second resin is produced by reacting 0.5 to 1.5 moles of the compound represented by Chemical Formula 10 with respect to 1 mole of the second base resin.

10. The (meth)acrylate resin according to claim 8, wherein the second resin is produced by a reaction of 0.1 mol to 1.0 mol of the compound represented by Chemical Formula 8 relative to 1 mol of the second base resin.

11. The first resin is ia) a first base resin comprising a repeating unit represented by the following formula 5; or ib) a reaction product of the first base resin and a compound represented by the following formula 6: iia) a compound represented by the following formula 7; or iib) a compound represented by the following formula 8; The second resin is ic) a second base resin including a repeating unit represented by the following formula 9; and iic) a compound represented by the following chemical formula 10; or iid) a compound represented by the following chemical formula 10 and a compound represented by the following chemical formula 8: 【Chemistry 4A】 【Chemistry 4B】 In the above Chemical Formula 5 to Chemical Formula 10, Each of R1 to R4 independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 15 carbon atoms; each of L1 and L2 independently represents a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 10 carbon atoms, a substituted or unsubstituted cycloalkenylene group having 3 to 10 carbon atoms, or a substituted or unsubstituted arylene group having 6 to 15 carbon atoms; * indicates a connection point.

12. A resin composition comprising the (meth)acrylate resin according to claim 1 and an additive.

13. The resin composition according to claim 12, wherein the additive comprises one or more of a photoinitiator, a thermosetting binder, an inorganic filler, a dispersant, a thermosetting binder catalyst, a pigment, a photocurable monomer, an ion scavenger, an antioxidant, and a filler.

14. A dry film solder resist comprising the resin composition according to claim 12 or a cured product of the resin composition.

15. 15. The dry film solder resist of claim 14, wherein an active ester group of the dry film solder resist reacts with an epoxy group of an epoxy molding compound (EMC) to increase adhesion between the dry film solder resist and the epoxy molding compound.

16. The adhesion between the dry film solder resist and the epoxy molding compound is 10 kgf / cm 2 ~100Kgf / cm 2 The dry film solder resist according to claim 14 ,

Citation Information

Patent Citations

  • Curable resin composition, molding material, and fuel cell separator

    JP2004346315A

  • Curable composition containing carboxyl-group-containing photosensitive resin

    JP2004359729A

  • Photocurable and thermosetting resin composition and dry film solder resist

    JP2018533652A

  • Acid group-containing (METH)acrylate resin, curable resin composition, cured product, insulation material and resist member

    JP2022052982A

  • Photocurable alkali developable cresol novolac epoxyacrylate resin and preparation thereof

    KR1020110126327A